A Case Report of Burning Mouth Syndrome Treated with Individualised Homeopathy - Gaertner, Katharina; Frei-Erb, Martin (Homeopathy, 2020)
Introduction Burning mouth syndrome (BMS) is a rare disease of unknown origin. No efficient treatment is known, and integrative approaches are warranted. So far, individualised homeopathy (iHOM) has not been evaluated or reported in any peer-reviewed journal as a treatment option.Methods At the Centre of Complementary Medicine at a university institute in Switzerland, a 38-year-old patient with BMS and various co-morbidities was treated with iHOM between July 2014 and August 2018. The treatment involved prescription of individually selected homeopathic single remedies. During follow-up visits, outcome was assessed with two validated questionnaires concerning patient-reported outcomes. To assess whether the documented changes were likely to be associated with the homeopathic intervention, an assessment using the modified Naranjo criteria was performed.Results Over an observation period of 4 years, an increasingly beneficial result from iHOM was noted for oral dysaesthesia and pains as well as for the concomitant symptoms.Conclusion Considering the multi-factorial aetiology of BMS, a therapeutic approach such as iHOM that integrates the totality of symptoms and complaints of a patient might be of value in cases where an association of psychological factors and the neuralgic complaints is likely.
Keywords: burning mouth syndrome; pain management; integrative medicine